Early Neurodevelopmental Findings Predict School Age Cognitive Abilities in Duchenne Muscular Dystrophy: A Longitudinal Study. - Daniela Chieffo; Claudia Brogna; Angela Berardinelli; Grazia D'Angelo; Maria Mallardi; Adele D'Amico; Paolo Alfieri; Eugenio Mercuri; Marika Pane (PLoS ONE)
Objective Neurodevelopmental and cognitive difficulties are known to occur frequently in boys with Duchenne muscular dystrophy but so far none of the published studies have reported both early neurodevelopmental assessments and cognitive tests in the same cohort. The aim of the present longitudinal study was to establish the correlation between early neurodevelopmental assessments performed in preschool boys and the cognitive scales performed at school age or later. Methods We performed cognitive tests at school age (mean age 5.7 year ±1.7 SD) (69 months+19 SD) in a cohort of Duchenne boys, previously assessed using the Griffiths scales before the age of 4 years (mean age when the Griffiths scales were performed 30 months ±8.9 SD). Results The range of total Developmental quotients on the Griffiths ranged between 56 and 116 (mean 89 ± 15.6 SD). The total Intelligence Quotients on the Wechsler scales ranged between 35 and 119 (mean 87 ± 17.2 SD). There was a significant correlation between the findings on the two scales. P = <0.0001. When we subdivided the cohort according to site of mutations, there was a difference between boys with mutations upstream exon 44 and those with mutations in exon 44-45 affecting Dp140 on both Developmental and Intelligence Quotient (p 0.01 and p 0,003 respectively). Conclusions Our results confirm that Duchenne boys tend to slightly underperform on both neurodevelopmental and cognitive assessments. Early neurodevelopmental findings correlated with the cognitive results obtained at school age with a clear concordance between subscales exploring similar domains on the two scales.